Interaction Effects of Life Events and Hair Cortisol on Perceived Stress, Anxiety, and Depressive Symptoms Among Chinese Adolescents: Testing the Differential Susceptibility and Diathesis-Stress Models - Xu, Youyun; Liu, Yapeng; Chen, Zheng; Zhang, Jing; Deng, Huihua; Gu, Jiexin (Frontiers in Psychology, 2019)
The present study aimed to examine whether the activity of the hypothalamic pituitary adrenal axis (HPA) can serve as a physiological marker of the differential susceptibility model or the diathesis-stress model by exploring the interactive effect of life events and hair cortisol on perceived stress, anxiety and depression symptoms among Chinese adolescents. Participants were 324 students in the senior high school. They reported their psychological states with questionnaires at their first semester after the three-month adaptation and provided their 1-cm hair segments closest to the scalp two weeks later. Hair cortisol concentration as a biomarker of the HPA activity was measured with high-performance liquid chromatography tandem mass spectrometry. The results revealed that the interaction between academic events and hair cortisol was significant in predicting adolescents’ perceived stress, anxiety and depression symptoms. There was also a significant interaction between interpersonal events and hair cortisol in predicting adolescents’ anxiety symptoms. The approach of region of significance, the proportion of interaction index and the proportion affected index revealed that adolescents with higher cortisol level were at risk for higher perceived stress and more anxiety symptoms under high academic events, and were in favor for lower perceived stress and less anxiety symptoms under lower academic events. Adolescents with higher cortisol level were in favor for less anxiety symptoms under higher interpersonal events, but were at risk for more anxiety symptoms under lower interpersonal events. Additionally, adolescents with higher cortisol level were at risk for more depression symptoms under higher academic events. These results suggested that the HPA activity might be a physiological marker of the differential susceptibility model for perceived stress and anxiety symptoms, and might be a physiological marker of the diathesis-stress model for depression symptoms among Chinese adolescents.